2002
DOI: 10.1128/jvi.76.21.10674-10684.2002
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Human Immunodeficiency Virus Type 1 Recombinants in a Patient with Rapid Progression to AIDS

Abstract: Although human immunodeficiency virus type 1 (HIV-1) recombinants have been found with high frequency, little is known about the forces that select for these viruses or their importance to pathogenesis. Here we document the emergence and dynamics of 11 distinct HIV-1 recombinants in a man who was infected with two subtype B HIV-1 strains and progressed rapidly to AIDS without developing substantial cellular or humoral immune responses. Although numerous frequency oscillations were observed, a single recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 66 publications
2
53
0
Order By: Relevance
“…Furthermore, the variables that may contribute to susceptibility or resistance to superinfection, such as the timing of exposure to a second virus or the immunologic status of the exposed individual, have not been well defined. It is also uncertain whether superinfection is invariably associated with the loss of HIV containment and clinical deterioration (8,17,21,23,26,27,30,60). Understanding the risks for and the biological consequences of HIV superinfection will not only clarify an important clinical problem, it may also provide important insights into the nature of the immune responses that may confer protection against the initial acquisition of HIV.…”
Section: Although There Were Transient Increases In Viral Loads Of Thmentioning
confidence: 99%
“…Furthermore, the variables that may contribute to susceptibility or resistance to superinfection, such as the timing of exposure to a second virus or the immunologic status of the exposed individual, have not been well defined. It is also uncertain whether superinfection is invariably associated with the loss of HIV containment and clinical deterioration (8,17,21,23,26,27,30,60). Understanding the risks for and the biological consequences of HIV superinfection will not only clarify an important clinical problem, it may also provide important insights into the nature of the immune responses that may confer protection against the initial acquisition of HIV.…”
Section: Although There Were Transient Increases In Viral Loads Of Thmentioning
confidence: 99%
“…Importantly, recombination can also pair advantageous mutations, which can facilitate the acquisition of multidrug resistance leading to treatment failure (48)(49)(50)(51)(52)(53)(54). Recombination may also be an important mechanism by which the virus eventually escapes immune control (55)(56)(57)(58). However, recombination also has the potential to inhibit adaptation and evolution depending on epistasis and genetic drift (51).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of individuals infected with more than one genetically distinct HIV-1 revealed that these patients often also harbor hybrid viruses in their viral populations (13,16,26,28,38,46). Intersubtype recombinants that cause epidemics in certain geographical areas have multiple break-off points along the genome (35).…”
mentioning
confidence: 99%
“…Of the more than 70,000 sequences that are catalogued in the HIV sequence database at the Los Alamos National Laboratory (http://www.hiv.lanl.gov), approximately 8% (Ͼ5,500) are classified as recombinants. Furthermore, recombinant strains of HIV-1 have been observed worldwide (13,16,26,28,38,46). The inherent ability of HIV-1 to recombine poses a constant problem for effective anti-HIV-1 treatment because multidrugresistant variants can be generated by recombining the genome of singly or weakly resistant viruses.…”
mentioning
confidence: 99%